EPISTOLARY OF ANDRIY CHAIKOVSKIY (1920-35) OV A SOURCE TO STUDY THE KOLOMYIA REGION OF THE BIOGRAPHY OF A WRITER - Vasylchuk, M.M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The informative possibility of the epistolary hemorrhage of Andriy Chaikovskiy, a famous Ukrainian writer and publicist, is opened by the author. Multiformity of informational lauers fixed in hit correspondence are shown in this article. Such poerly investigated guestions of follows: the removing circumstances to Kolomyia, everyday life arrangement are touched by the researcher. Simultaneously the attention is paid to conditions and creative work circumstances of the artist, and the circle of his addressee and so on, and so forth.